Efisiensi Pembiayaan Pendidikan sebagai Strategi Peningkatan Mutu di Sekolah Dasar: Studi Kasus SDN Mekarjaya - Rinrin Oktariani; Riswandi Hilman; Ismawati Emalia; Lilis Kholisoh Nuryani; Asep Budi Tauhid (CV. ALIM'SPUBLISHING, 2026)
Educational financing management plays an important role in improving the quality of education in primary schools. However, limited school operational funds often become an obstacle to achieving optimal educational outcomes. This study aims to analyze the efficiency of educational financing as a strategy for improving education quality at SDN Mekarjaya, Tasikmalaya Regency. The research employed a qualitative descriptive approach with a case study design. Data were collected through interviews, observations, and documentation studies involving the principal, teachers, and school financial documents. The findings indicate that the implementation of data-based planning, priority-scale budgeting, digital financial administration through the ARKAS application, and collaboration with various stakeholders contributed positively to improving school quality. Financing efficiency supported literacy programs, teacher competency development, learning effectiveness, and school management improvement. Although the school still faced challenges related to limited funding sources and administrative constraints, efficient financial management enabled the school to optimize available resources effectively. This study concludes that efficient, transparent, and accountable educational financing management can serve as a strategic instrument in supporting sustainable improvement in the quality of primary education.